2007
DOI: 10.1063/1.2762282
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical corrosion behavior of a Zr-based bulk-metallic glass

Abstract: Using cyclic-anodic-polarization tests, the corrosion behaviors of the as-cast, deformed, and relaxed Zr52.5Cu17.9Ni14.6Al10.0Ti5.0 bulk-metallic glasses were investigated. Their corrosion behaviors are related to the amount of free volume. As the free volume decreased, the glasses became more corrosion resistant. The as-cast and the deformed glasses are less resistant to pit propagation, while the relaxed one is more vulnerable to pit nucleation. It is thought that an increase in free volume favors the pit pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(32 citation statements)
references
References 15 publications
2
30
0
Order By: Relevance
“…Several studies on aqueous corrosion of glass-forming alloys, e.g. FeCSiBPCrAlMo [11], NiNb [12] and ZrCuNiAlTi [13], suggested an enhanced corrosion resistance on structurally relaxed metallic glasses as indicated by the significantly improved passivation behaviours. Ni-Nb-Ti-Zr-Co bulk metallic glasses possess not only high glass-forming ability but also extremely high corrosion resistance and good mechanical properties [14][15], which are promising materials for the applications in extremely aggressive solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on aqueous corrosion of glass-forming alloys, e.g. FeCSiBPCrAlMo [11], NiNb [12] and ZrCuNiAlTi [13], suggested an enhanced corrosion resistance on structurally relaxed metallic glasses as indicated by the significantly improved passivation behaviours. Ni-Nb-Ti-Zr-Co bulk metallic glasses possess not only high glass-forming ability but also extremely high corrosion resistance and good mechanical properties [14][15], which are promising materials for the applications in extremely aggressive solutions.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, nickel and beryllium free Zr-and Ti-based BMGs were considered. [10][11][12][13][14] However, these alloy systems have relatively lower glass-forming ability when compared with the multicomponent BMGs such as the ZrTiCuNiBe BMG series. Ni or Be elements are often necessary to enhance the glass formability as their use can introduce large atomic size difference when compared with other elements such as Zr.…”
Section: Introductionmentioning
confidence: 99%
“…These corrosion currents are significantly lower than those obtained in the case of the 316L stainless steel [27]. Further enhancement of the corrosion resistance could be achieved as several studies on aqueous corrosion of glass-forming alloys suggested [28,29] on structurally relaxed metallic glasses. The improved resistance of amorphous alloys is not only based on their structure itself but also on their ability to promote amorphous oxide formation.…”
Section: Interdisciplinary Research In Engineering: Steps Towards Brementioning
confidence: 78%